Factors Affecting Choosing Peritoneal Dialysis Modality among Hemodialysis Patients in Single Center Study, Taif region, KSA - Alhomayani, Faisal; Alsuwat, Mohammed; Sarriyah, Abdulhameed; Alotaibi, Hamoud; Almnjwami, Rakan; Althobaiti, Hazem; Alsharif, Abdullah (International Journal of Innovative Research in Medical Science, 2021)
Background: Renal replacement care of choices for end-stage renal disease (ESRD) patients include chronic dialysis either hemodialysis or peritoneal dialysis and kidney transplantation, the vast majority of patients use hemodialysis (HD) rather than peritoneal dialysis (PD). Methods: This is a single center cross sectional observational study in the King Abdul-Aziz Specialist Hospital, Taif, Saudi Arabia. The study was conducted from 20 October 2020 to 20 July 2021. The participants 135 patients, A survey was prepared by specialized authors, and self-answered by hemodialysis patients after informed consent was approved by the participants to complete the survey. Statistical analysis was conducted using SPSS version 21. Result: Factors affecting choosing Peritoneal Dialysis modality among Hemodialysis patients in a single center among Saudi population were analyzed in the total number of cases 135 including 52% are males, 47.9% are females, presence of chronic diseases among our cases Hypertension, followed by Diabetes were the most important causes for the etiology of chronic kidney disease in (51%, 33.3%), peritoneal dialysis was discussed with the majority of cases (59.4%), The higher percentage of our participants deny any mental illness, eye disease, hernia or abdominal surgery or ischemic bowel disease.if PD modality was discussed with them and correlated with reasons for not picking PD, this was statistically significant proved by Pearson Chi square test with Confidence interval 95%, P value <0.05. Conclusion: This study indicates that the cardinal patients' characteristics of young age, single, being ambulant, if PD was discussed with the patient are among the factors influencing choosing peritoneal dialysis among haemodialysis patients.